THE INFLUENCE OF THE ROLE OF KSU GAPOKTAN ALBASIKO II ON THE INCREASE OF COOPERATIVE MEMBERS' INCOME: (Case Study of Simpang Tiga Bedeng, Luhak Nan Duo) - Febria Anggie Saputri; Yossi Eriawati; Fawza Rahmat (Transpublika Publisher, 2023)
This study was conducted at the Cooperative of Multiple Enterprises (KSU) GAPOKTAN ALBASIKO II Branch in Simpag Tiga Bedeng, Luhak Nan Duo. The research aims to determine whether the variable of cooperative role influences financial performance. It is quantitative research employing data gathered through interviews, questionnaire distribution, and observation. The data analysis technique employed is simple linear regression. The study employed primary data obtained through a questionnaire administered in field research setting with a total of 50 respondents. The population for this research comprised the members of the Cooperative of Multiple Enterprises (KSU) GAPOKTAN ALBASIKO II. Data collection was conducted using field research methods (questionnaires and literature review). The results of this study indicate that the cooperative's role does not influence member income. This is evident from the coefficient of determination of 0.193, signifying the contribution of the cooperative's role to member income. With a significance level of 5%, the calculated F value is 1.848, with a significance level of 0.180, leading to the rejection of the null hypothesis (HO) and acceptance of the alternative hypothesis (Ha). Thus, the cooperative's role does not affect member income.